Optimization of Career Development Through Transformation of Functional Position of Customs and Excise Inspector at Indonesian Customs - Aulia Achyar Mubarok (Journal of Accounting and Finance Management, 2022)
The transformation of administrative positions into functional positions is one of the implementations of bureaucratic simplification that has been and continues to be carried out at the Directorate General of Customs and Excise of the Republic of Indonesia.This article discusses the optimization of career development in Functional Positions in order to simplify the bureaucracy through the transformation of administrative positions into Functional Positions of Customs and Excise Inspectors.The research method used in this paper is descriptive qualitative with library research data collection techniques in the form of reviewing legislation on transformation position, national bureaucratic reform, functional positions of customs and excise inspectors, as well as collecting material from books, journals, and other open source. The limitation in this article is that there is still little research literature on FPCEI, so it is hoped that this article can be a reference material in writing the next article by adding other variables.The results of the study show that the transformation of administrative positions into functional positions at the DGCE of the Republic of Indonesia has gone well, but optimization of the career development system is still needed in the context of career development through the transformation of administrative positions into Functional Positions of Customs and Excise Inspectors.